The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5539/elt.v5n2p134
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in the Iranian High School EFL Textbooks

Abstract: Gender bias is unfortunately still present in many societies especially the developing countries. Such prejudice is in most cases in favor of males and against females. While females nowadays comprise a great majority of the work force all around the world, they are still being looked upon as the weaker sex associated with stereotypical roles as stay-at-home mothers whose main task is to breed children, wash the dishes, etc.Such prejudice if present in a society gets manifested in its EFL/ ESL materials. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 65 publications
6
49
1
2
Order By: Relevance
“…Similar findings are reported by Amini & Birjandi (2012). The study examines gender bias in two Iranian high school textbooks and concludes that "sexism is still vividly practiced in Iranian EFL materials" (p. 138).…”
Section: Previous Studiessupporting
confidence: 67%
“…Similar findings are reported by Amini & Birjandi (2012). The study examines gender bias in two Iranian high school textbooks and concludes that "sexism is still vividly practiced in Iranian EFL materials" (p. 138).…”
Section: Previous Studiessupporting
confidence: 67%
“…Book designers need to be aware of sexuality in their books; they must pay more attention to the norms of their society and the changing movements which are to be seen in their society. Therefore, they need to try to include these elements in the design of their books, since textbooks reflect the social, cultural and religious ideologies and perceptions of their writers (Amini & Birjandi, 2012). Furthermore, book designers and developers must develop materials in such a way that these learning tools "engage students in a "gender critique" by encouraging critical questioning of biases in the facts and theories presented" (Hayibor & Peterat, 1995, p. 103).…”
Section: Discussionmentioning
confidence: 99%
“…As far as the researchers know, no research has been done before on these books using social semiotics, and for that reason the researchers tried to analyze the English One books in terms of gender from a semiotics point of view. Amini and Birjandi (2012) have examined the extent and types of gender bias in two of the most used EFL textbooks at the high school level in Iran. Sexism was investigated in five categories -including visibility, generic masculine constructions, occupations linked by gender and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Within children's textbooks used in several Iranian language learning centers, Parham (2013) found that while female figures initiate conversations more frequently than males, they are less represented compared to their male counterparts. This extends up to secondary level in Iran according to an earlier work by Amini and Birjandi (2012). According to their examination of high school EFL textbooks, women are likewise obscured in both visual and textual depictions.…”
Section: Effects Of Gender Stereotyping On Childrenmentioning
confidence: 99%